2014
DOI: 10.3201/eid2009.131668
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis jiroveciiPneumonia in Patients with or without AIDS, France

Abstract: Immunosuppressed patients without AIDS had longer time to treatment and a higher rate of death than did patients with AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
241
4
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(265 citation statements)
references
References 27 publications
(41 reference statements)
11
241
4
9
Order By: Relevance
“…Studies in the early 2000s reported an incidence of PCP among HIV-infected individuals below 1 case per 100 person-years [2-8]. Given the trend towards earlier diagnosis of HIV infection and immediate ART independent of CD4+ T cell count, the incidence of PCP in HIV patients has likely decreased further during recent years [9-12]. …”
Section: Epidemiology and Risk Groupsmentioning
confidence: 99%
“…Studies in the early 2000s reported an incidence of PCP among HIV-infected individuals below 1 case per 100 person-years [2-8]. Given the trend towards earlier diagnosis of HIV infection and immediate ART independent of CD4+ T cell count, the incidence of PCP in HIV patients has likely decreased further during recent years [9-12]. …”
Section: Epidemiology and Risk Groupsmentioning
confidence: 99%
“…PCP often occurs in HIV-infected patients, but frequency of PCP in other immunocompromised populations, such as patients with kidney transplantation, is increasing (1-3). Common clinical manifestations and outcomes of PCP between HIVpositive and HIV-negative patients are well known; in non-HIVinfected patients symptomatology is more acute, mortality is generally higher, and fungal burden is lower (2,4). In any case, biological diagnosis of PCP is required, and the microscopic identification of P. jirovecii (cysts and trophic forms) by staining bronchoalveolar lavage (BAL) samples continues to be the most widely used method.…”
mentioning
confidence: 99%
“…The clin-ical presentation of PCP in HIV-negative patients is more severe than in HIV-positive patients, leading to estimated mortality rates of 40% and 15%, respectively (20)(21)(22). This is probably due to differences in the pathophysiology of the disease, and particularly in the host immune response.…”
mentioning
confidence: 99%